Epidemiology of hypertension among urban population in Golestan province in north of Iran - Abdollahy AA; Bazrafshan HR; Salehi A; Behnampour N; Hosayni SA; Rahmany H; Yazdi Kh; Sanagoo A (مجله دانشگاه علوم پزشکی گرگان, 2007)
Background&Objective: High blood pressure (BP) is one of the most important health problem world-wide (2005), and risk factor of cardiovascular diseases. This study was determine the prevalence of high blood pressure (BP) among urban subjects in Golestan of province, during 2005. Materials&Methods: This cross sectional study was done on 5000 subjects of 17-70 years old in different towns of Golestan province during 2005. Two equal ratios of both sexes were selected on random clustering sampling in the morning and afternoon. A questionnaire consisting of demographic data and clinical information such as electronic presser gauge filled by trained persons. All of the data analyzed using spss-11.5 and descriptive statistics. Results: The result showed that 2500 male (50%) and 2500 (50%) female, ethenicity were (4.6%) Torkaman, (18.9%), and Sistani (76.4%) Fars group from age of 17 to 70 years old. This study on this basis criterion JNC-5 (46.4%) all of studied subjects had blood pressure normal, (22.6%) blood pressure high normal (21.4%), blood pressure light (7.4%), blood pressure medium and (2.2%) blood pressure severe. Conclusion: The prevalence high blood pressure among the urban population in this province in this province was 31%. Which is slightly higher than other regions in Iran and other part of the world. This issue can be considered in the health planing and theraputic programs in the region.